First insights into the intestinal microbiota of the endangered Angler Saddleback pig - Stéphanie Céline Hornburg; Marvin Suhr; Corinna Bang; Dirk Hinrichs; Stefanie Klingel; Georg Thaller; Anna Olschewsky (PLoS ONE, 2026)
The Angler Saddleback pig is an endangered local breed from northern Germany, characterized by high genetic diversity and exceptional meat quality, but with reduced growth performance compared to commercial pigs. As intestinal microbiota is known to influence health, metabolism, and fat deposition, this study aimed to provide the first characterization of the gut microbial community of this breed. Fecal samples from 37 Angler Saddleback pigs, raised under semi-controlled conditions and fed a restricted diet supplemented with grass-clover silage, were collected at slaughter. Bacterial community composition was analyzed by 16S rRNA gene amplicon sequencing and evaluated using QIIME2, followed by statistical analyses of alpha and beta diversity. The intestinal microbiota was highly diverse, with Bacteroidota (49.5%) and Firmicutes (34.3%) as the dominant phyla, complemented by Spirochaetota and Proteobacteria. Core taxa included Lactobacillus amylovorus , Prevotella , and Streptococcus, while strong inter-individual variability was observed. Beta diversity analysis revealed significant effects of breeder and fattening period on microbial composition, whereas sex, age, and maternal lineage showed no significant influence. These findings suggest that both diet and early-life environment shape the intestinal microbiota of Angler Saddleback pigs. The study provides a foundation for exploring microbiota-associated traits that may contribute to conservation and breeding strategies for this endangered pig breed.